THE PHENOMENON OF ISLAMIC EDUCATION IN MUSLIMS COUNTRIE - Muhammadong, Muhammadong; Ichsani, Ichsani; Yasriuddin, Yasriuddin; Wahyudin, Wahyudin; Husain, Husriani (Academy of Education Journal, 2023)
The aims of this research is to find out the phenomenon of Islamic education in Muslim countries. In general, Islamic education is education that is oriented towards the teachings of the Qur'an and the hadith of the Prophet saw. Islamic education is not only taught in the formal legal system which is carried out regularly but becomes a teaching that must be implemented in social life. In Muslim countries, Islamic Education is used as a formal education that must be completed based on government regulations. It is undeniable that Islamic education in Muslim countries has adopted a system of modernity so that Islamic education is oriented towards fulfilling physical needs. However, with this modernity, Islamic Education takes on a role as a practical function in realizing Islamic teachings as the absolute truth of Allah SWT.